DEVELOPMENT OF THE DIGITAL ECONOMY IN UZBEKISTAN - Abdurakhmonov Abdulaziz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In a rapidly developing century, indicators of the development of digital technologies and the digital economy of Uzbekistan. Some laws of digitalization in recent years.